2021
DOI: 10.3390/cancers13194937
|View full text |Cite
|
Sign up to set email alerts
|

Organ-Specific Uptake of Extracellular Vesicles Secreted by Urological Cancer Cells

Abstract: Extracellular vesicles (EVs) secreted by cancer cells have been shown to take a pivotal part in the process of local and systemic tumor progression by promoting the formation of a supportive local tumor microenvironment and preparing premetastatic niches in distant organ systems. In this study, we analyzed the organ-specific uptake of EVs secreted by urological cancer cells using an innovative in-vivo approach. EVs from benign and malignant prostate, kidney, and bladder cells were isolated using ultracentrifug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Finally, whether EVs generated in vitro could be used as next-generation therapeutic approaches, such as alternative viruses or synthetic nanovectors, for organ-targeted biotherapies. Addressing the first challenge requires to find organ-specific EVs or craft strategies to use novel technologies to label organ-specific EVs in appropriate animal models (Chand et al 2020 ; Linxweiler et al 2021 ). The next challenge may require the generation of genetic animal models with organ-specific defects in the production of EVs.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, whether EVs generated in vitro could be used as next-generation therapeutic approaches, such as alternative viruses or synthetic nanovectors, for organ-targeted biotherapies. Addressing the first challenge requires to find organ-specific EVs or craft strategies to use novel technologies to label organ-specific EVs in appropriate animal models (Chand et al 2020 ; Linxweiler et al 2021 ). The next challenge may require the generation of genetic animal models with organ-specific defects in the production of EVs.…”
Section: Discussionmentioning
confidence: 99%
“…These PCa-derived sEVs may play a significant role in regulating communication between tumor cells, the tumor microenvironment (TME), and distant metastasis sites through both autocrine and paracrine mechanisms [ 74 ]. This promotes signal transduction and the formation of pre-metastasis niches (PMNs), ultimately contributing to tumor development and metastasis [ 75 ]. Notably, cancer cells require sufficient oxygen to grow, and studies indicate that cancer-derived sEVs serve as carriers of various proteins, RNAs and lipids, which re-program the secretion of growth factors and cytokines by endothelial cells, activate signaling pathways, and prompt perivascular cell migration and the formation of new blood vessels [ 76 ].…”
Section: Mechanisms Of Sev Proteins In Tumor Microenvironment and Pro...mentioning
confidence: 99%
“…Exosomes secreted by metastatic cancer cells could be preferentially uptaken by specific host organ to organize the pre-metastatic niche via upregulation of proinflammatory gene expression and immunosuppressive cytokine, which leads to organotropic metastasis [ 98 ]. The amount and origin of EVs affect their organ-specific uptake during metastasis as the rate of EV uptake secreted by malignant cancer cells is more than benign cancer cells [ 99 ]. It has also been shown that targeting the integrins α6β4 and αvβ5 of exosomes reduced their uptake and metastasis to lung and liver, respectively [ 83 ].…”
Section: Extracellular Vesicle (Ev) Uptake Customization By Novel Ev ...mentioning
confidence: 99%